Phytochemical investigation, molecular docking studies and DFT calculations on the antidiabetic and cytotoxic activities of Gmelina philippensis CHAM. (1st March 2023) - Sayed, Hanaa M.; Ahmed, Amany S.; Khallaf, Iman SA.; Qayed, Wesam S.; Mohammed, Anber F.; Farghaly, Hanan S.M.; Asem, Ayman
Abstract: Ethnopharmacological relevance: Gmelina philippensis CHAM is an ornamental plant that is distributed in South Asia and warm regions of the Mediterranean area. The plant is traditionally applied in folk medicine for the treatment of diabetes. Aim of the study: To evaluate the cytotoxic and the antidiabetic activities of the ethanolic extract of G. philippensis aerial parts. To isolate the metabolite(s) responsible for these activities and to elucidate the mechanism of action by molecular docking study. Materials and methods: Compounds (1–11 ) were isolated using various chromatographic techniques and their structures were determined by NMR spectroscopic and mass spectrometric analysis. The cytotoxic effect was tested using viability test and MTT assay. Antidiabetic activity was evaluated by measuring the inhibitory activity of the ethanolic extracts and compounds against α-glucosidase and α-amylase activities. Modeling and docking simulations were performed using Molecular Operating Environment software and the crystal structure of protein kinases CDK2, (1PYE) and AKT1 (4GV1), in addition to α-glucosidase (3TOP) and α-amylase (2QV4). Results: Compounds 2, 3 and 8 were isolated for the first time from the plant and identified as: gmelinol (2 ), apigenin (3 ) and tyrosol (8 ). While β -sitosterol-3- O - β -D-glucopyranoside (4 ) vicenin-II (7 ), rhoifolin (9 ), isorhoifolin (11 ) were isolated for the first time from the genus, along with and the new iridoid 6- O-α -L-(2″- O -benzoyl-4″- O - trans - p -methoxycinnamoyl)rhamnopyranosyl-1α- β -D-glucopyranoside catalpolgenin (6 ). In addition, to the previously reported compounds: mixture of β -sitosterol and stigmasterol (1 ), and 6- O- α-L-(2″, 3″, 4″-tri- O -benzoyl)rhamnopyranosylcatalpol (5 ) and 6- O-α -L-(2″- O - trans - p -methoxycinnamoyl)rhamnopyranosylcatalpol (10 ). The cytotoxic activity against hepatocellular carcinoma (HepG-2) cell lines for compounds 2, 5, 7, 9 and 11 was conducted using cisplatin as a standard. Gmelinol (2 ) exhibited strong cytotoxic activity against HepG-2 cell lines with IC 50 value of 3.6 ± 0.1 μg/ml which is more potent than the standard cisplatin IC 50 = 8.7 ± 0.9 μg/ml. Molecular modeling of 2 against diverse targets of protein kinases suggested that CDK-2 and AKT-1 could be the dual probable kinase targets for its cytotoxic action. Compound 2 showed α-amylase inhibition activity with IC 50 value of 60.9 (μg/ml) while, compounds 5 showed strong α-glucosidase inhibition activity with IC 50 values of 41.7 (μg/ml) compared to acarbose with IC 50 value of 34.7, 30.6 (μg/ml). Molecular docking of compounds 2 and 5 on α-glucosidase (3TOP) and α-amylase (2QV4) enzymes revealed high binding affinity and active site interactions comparable to native ligand acarbose. Conclusion: The ethanolic extract of G . philippensis CHAM aerial parts is effective against HepG-2 cell lines, α-amylase and α-glucocidase activities. Biologically guided isolation indicated that compounds 2 and 5 are responsible for these activities. These results were supported by DMF calculations that detected the molecular areas responsible for protein interactions shown via docking studies. Graphical abstract: Image 1 Highlights: Isolation and identification of compounds from G. philippensis aerial parts. In vitro cytotoxic activities of the major compounds against HepG-2 cell line. In vitro antidiabetic activities of the main compounds. Modeling and docking simulations of gmelinol and protein kinases (CDK-2 and AKT1). Docking simulations of compounds 2 and 5 with α-amylase and α-glucosidase enzymes.